2015
DOI: 10.2139/ssrn.2577961
|View full text |Cite
|
Sign up to set email alerts
|

Where the Risks Lie: A Survey on Systemic Risk

Abstract: We review the extensive literature on systemic risk and connect it to the current regulatory debate. While we take stock of the achievements of this rapidly growing field, we identify a gap between two main approaches. The first one studies different sources of systemic risk in isolation, uses confidential data, and inspires targeted but complex regulatory tools. The second approach uses market data to produce global measures which are not directly connected to any particular theory, but could support a more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
147
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(154 citation statements)
references
References 176 publications
(22 reference statements)
2
147
0
5
Order By: Relevance
“…We interact the beta coefficient with a measure of total size for two reasons. First, it can be shown that MES (our second measure) is an affine function of the CAPM beta (see Section 5 in Benoit et al (2015)) if a single factor model describes asset returns. By interacting a beta coefficient with size we break this (trivial) link.…”
Section: Dollar Systematic Risk (β×Mv)mentioning
confidence: 99%
See 2 more Smart Citations
“…We interact the beta coefficient with a measure of total size for two reasons. First, it can be shown that MES (our second measure) is an affine function of the CAPM beta (see Section 5 in Benoit et al (2015)) if a single factor model describes asset returns. By interacting a beta coefficient with size we break this (trivial) link.…”
Section: Dollar Systematic Risk (β×Mv)mentioning
confidence: 99%
“…Our sample of listed financial sector firms contains commercial banks, insurers, asset managers, and broker/dealers. In terms of ranking methodologies, we consider risk rankings based on criteria such as SRISK (Acharya, Engle, and Richardson, 2012;Brown-lees and Engle, 2015), MES (Acharya, Pedersen, Philippon, and Richardson, 2010), the leverage ratio (Fostel and Geanakoplos, 2008;IMF, 2009;Geanakoplos and Pedersen, 2014), systematic risk defined as the so-called CAPM beta times market capitalization (Benoit, Colliard, Hurlin, and Pérignon, 2015), ∆CoVaR (Adrian and Brunnermeier, 2014;Castro and Ferrari, 2014), and firm's Value-at-Risk (Adams, Füss, and Gropp, 2014;White, Kim, and Manganelli, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Giglio et al (2015) compare 19 different systemic risk rankings via a principal components analysis. Interestingly, Benoit et al (2015) compare a number of these methodologies in a simplified analytical framework. They show that under specific conditions the Marginal Expected Shortfall (MES) of a firm as introduced by Acharya et al (2010) is proportional to its beta multiplied by the expected shortfall of the market.…”
Section: Other Ranking Methodsmentioning
confidence: 99%
“…Systemic risk allocation has, for example, been embedded into formal regulation by labeling some financials as Systemically Important Financial Institutions (SIFIs) subject to increased capital requirements. Different methods have been put forward to distinguish SIFIs from non-SIFIs using so-called systemic risk rankings; see Benoit et al (2015) for a recent survey. Most of these ranking methodologies make use of readily available data and simple statistical measures, such stock betas, volatilities, (tail) dependence measures, (conditional) values-at-risk, etc.…”
Section: Introductionmentioning
confidence: 99%